Smart interfaces in Li-ion batteries: Near-future key challenges. (20th May 2022) - Pargoletti, Eleonora; Arnaboldi, Serena; Cappelletti, Giuseppe; Longhi, Mariangela; Meroni, Daniela; Minguzzi, Alessandro; Mussini, Patrizia Romana; Rondinini, Sandra; Vertova, Alberto
Abstract: The recent impressive growth of Li-ion batteries (LIBs) production infrastructures is related to the surge of electric automotive industry. However, the current performance of LIBs is limited by the intrinsic capacity of graphite anodes, the use of organic solvents and by the limited wettability of the separator. In this review, we aim at demonstrating the grade of advance that can be expected for the performances of Li-ion batteries in the short term (roughly, 5–10 years) thanks to introduction of smart materials and interfaces. This temporal limit reflects the need of maintaining the current production chain of LIBs and optimizing the relative investments. In particular, we analyze and discuss the most recent scientific findings on: (i) the solvent, focusing our attention on deep eutectic solvents and ionic liquids (ILs) as an alternative to the currently adopted organic solvents; (ii) tuning the wettability of the separator, thanks to the optimization of the material, its porosity and its surface features; (iii) the anodic materials, according to the different proposed mechanism for Li storage and classifying them into different categories (i.e. carbon-based, Si, perovskites). Finally, we must recognize that, among the so-called "post LIBs" batteries, Li metal batteries can also play a key role in the near future: this type of battery is currently under production for primary cells but requires a smart cathode|electrolyte interface to avoid Li dendrite growth during charge/discharge cycles in their future as secondary systems.